Unforeseen cytomegalovirus retinopathy following high dose thiotepa and proton irradiation in a pediatric patient with high-risk medulloblastoma: A case report - Bigagli, Elisabetta; Agostiniani, Sara; Pugi, Alessandra; Rombi, Barbara; Tornaboni, Elena Eve; Censullo, Maria Luigia; Gori, Carlotta Gemma; Pavone, Rossana; Sardi, Iacopo (Frontiers in Pediatrics, 2023)
In immunocompetent individuals, cytomegalovirus (CMV) infection is usually mild but may cause severe complications such as retinitis, pneumonitis, and encephalitis in immunocompromised individuals. So far, cases of CMV retinitis in patients with medulloblastoma undergoing chemotherapy and radiotherapy, have not been reported. We herein report the case of a pediatric patient with high-risk medulloblastoma who experienced an unexpected CMV retinopathy and leukoencephalopathy following high dose thiotepa and proton irradiation. The patient underwent a four-course induction therapy (1st cycle: methotrexate and vinorelbine; 2nd cycle: etoposide and hematopoietic stem cells apheresis; 3rd cycle: cyclophosphamide and vinorelbine; 4th cycle: carboplatin and vinorelbine) and then a consolidation phase consisting in high dose thiotepa followed by autologous HSC transplant and proton cranio-spinal irradiation plus boost to the primary tumor site and pituitary site with concomitant vinorelbine. After two months of maintenance treatment with lomustine and vinorelbine, the patient showed complete blindness and leukoencephalopathy. A diagnosis of CMV retinopathy was made and oral valganciclovir was administered. CMV retinopathy was judged to be possibly related to the use of high dose thiotepa worsened by radiotherapy. This case suggests that in pediatric patients undergoing immunosuppressive chemo-radiotherapy, CMV reactivation should be carefully monitored to prevent serious complications such as retinopathy and visual loss.